Identification of Sanitation and Hygiene Risk Factors on the Incidence of Stunting in Indonesia: A Scoping Review - Heni, Heni; Idaningsih, Ayu; Wianti, Arni; Setyawati, Anita (CV. Strata Persada Academia, 2025)
Stunting is a critical public health challenge in Indonesia, where over 30% of children under five are affected. This scoping review aims to identify sanitation and hygiene (WASH) risk factors associated with stunting prevalence in Indonesia over the past decade. Using the Joanna Briggs Institute methodology and PRISMA-ScR guidelines, relevant studies were systematically identified, analyzed, and synthesized. Findings reveal a strong link between stunting and inadequate WASH conditions, including limited access to clean water, poor sanitation infrastructure, and inconsistent hygiene practices like handwashing with soap. Key challenges include the prevalence of open defecation, improper waste management, and reliance on unimproved water sources, particularly in low-income households. These conditions contribute to chronic diarrhea and environmental contamination, exacerbating stunting risks. Women are pivotal in mitigating these risks through improved hygiene, nutrition, and parenting practices. To combat stunting effectively, targeted interventions should focus on expanding access to clean water, enhancing sanitation infrastructure, and fostering behavioral changes in hygiene practices. Community-based programs and policies emphasizing women’s education and empowerment, alongside integrated WASH initiatives, are crucial for sustainable reductions in stunting prevalence and promoting child health in Indonesia.